Stress analysis of a centrally fractured rib fixated by an intramedullary screw - Liovic, P.; Sutalo, Ilija; Marasco, S. (Taylor & Francis, 2012)
The stress on an intramedullary screw rib fixation device holding together a centrally fractured human rib under in vivo force loadings was studied using finite element analysis (FEA). Validation of the FEA modelling using pullout from porcine ribs proved FEA to be suitable for assessing the structural integrity of screw/bone systems such as rib fixated by a screw. In the human rib fixation investigation, it was found that intramedullary bioresorbable Bioretec screws can fixate centrally fractured human ribs under normal breathing conditions. However, under coughing conditions, simulation showed Bioretec fixating screws to bend substantially. High stresses in the screw are mainly the result of flexion induced by the force loading, and are restricted to thin regions on the outside of the screw shaft. Stiffer screws result in less locally intense stress concentrations in bone, indicating that bone failure in the bone/screw contact regions can be averted with improvements in screw stiffness.